Molecular Phylogenetic Screening of Withania somnifera Relative From Indonesia Based on Internal Transcribed Spacer Region - Topik Hidayati; Didik Priyandoko; Putri Yunitha Wardiny; Dina Karina Islami (Bogor Agricultural University, Indonesia, 2016)
Withania somnifera (family Solanaceae), known commonly as Ashwaganda, is one of the important medicinal plants, and recent studies reported that Withanone, one of the chemical components in this plant, has ability to kill cancer cell. Because of endemic state of this plant to South Asia, exploring plant species under the same family which grow well in Indonesia has been of interest. The purpose of this study was to screen the Indonesian plant which has strong phylogenetic relationship with Ashwaganda. Thus, phylogenetic analysis using DNA sequences of internal transcribed spacer (ITS) region was conducted. Thus, 19 species of Solanaceae and two species of Convolvulaceae as outgroup were examined. Five ITS regions of Ashwaganda retrieved from GenBank were included in the phylogenetic analysis. Parsimony analysis showed that Indonesia Solanaceae comprises seven groups which is consistent with the global Solanaceae relationship as previously reported. Furthermore, our study revealed that two species, Physalis angulata and Physalis peruviana, are relative to W. somnifera. Morphologically, they share characters of flower and fruit. This result indicated that these two species are potential to have similar chemical properties as Ashwaganda, thus we can have new variants of Withanone originated from Indonesia with similar effect.